Propriedades tecnológicas da madeira de Tetrorchidium rubrivenium Poeppig & Endlicher - Guma, Rosana Lamana (2013)
This work aims to describe the wood anatomy, study the physical characteristics and verify its variation along the tree height, and determine the mechanical properties of Tetrorchidium rubrivenium (Euphorbiaceae) wood, to identify possible uses of this material. Tetrorchidium rubrivenium, of popular name canemaçu, is an arboreal species of Euphorbiaceae botanical family, Crotonoideae subfamily, which is a native species poorly studied. Five trees of this specie were cut in Vale do Sol, Rio Grande do Sul State, Brazil. Environmental license for obtainment of this material was issued according current legislation. Samples of this material were prepared for confection of histologic and quantitative fiber slides, used to describe wood anatomy. Predetermined sized samples were also prepared for the following tests: green and basic specific density, green moisture content, radial and tangential shrinkage, shear, parallel and perpendicular compression, hardness, static and impact bending. The canemaçu wood is composed mostly by fibers and rays, and in lower portion by axial parenchyma and vessels. These anatomic characters agree with expected features for canemaçu family and subfamily. Basic specific density of wood was 0.4062 g/cm3, and presented significant relationship with the position in relation to commercial height of the tree. Similar relationship was found with green specific density, green water content and radial and tangential wood shrinkages. The wood of canemaçu presented low mechanical resistance for parallel compression, hardness and static bending, and median shear resistance. The mechanical properties of canemaçu wood were also related with specific density at 12% moisture and significant relationship was observed with perpendicular compression, radial and tangential hardness, modulus of elasticity, modulus of rupture, work to maximum load in bending and resilience coefficient. Predictive models in function of specific density at 12% moisture were adjusted for these mechanical properties. In according with results of this study, the wood of canemaçu is appropriate to be used on furniture, particleboard, crates and general packaging, and on the manufacture of decorative items, internal finishing and toys.